PERSONALIZED PHARMACOLOGICAL CORRECTION OF IMMUNE SYSTEMS, METABOLIC AND NEUROPSYCHIC PARAMETERS IN CHRONIC BRAIN ISCHEMIA OF STAGE I AND II ON THE BACKGROUND OF HYPERTENSION DISEASE - A. I. Konoplya; A. A. Shulginova; N. A. Bystrova; V. P. Gavrilyuk; G. N. Ryzhikova (Медицинская иммунология, 2021)
The study aimed to develop a personalized pharmacological correction of immune, metabolic and neuropsychiatric disorders in chronic cerebral ischemia (CCI) stages I and II. The study included 104 patients, of which 76 were female and 28 were male, with CCI on the background of grade II hypertension, of which 52 patients were with stage I and 52 with stage II at the age of 50±5 years. Clinical and laboratory parameters were studied in 22 healthy donors of the same age who formed a control group. Patients with CCI were randomized according to gender, age, treatment method, concomitant pathology, and duration of the disease. Evaluation of clinical and laboratory data was carried out at the beginning of treatment and 2 weeks after its end. The sorption capacity of erythrocytes and the sorption capacity of the glycocalyx (SEG), the activity of lipid peroxidation processes, the state of the antioxidant system were determined in blood plasma and erythrocytes, the level of stable metabolites of nitric oxide (SMNO), neopterin, C-reactive protein, cytokines (TNFα, IL-1β, IL-8, IFNγ, IL-18, G-CSF, IL-4, IL-10), immunoglobulins (IgM, IgG, IgA), complement system components (C3, C4, C5, C5A), phagocytic and oxygen-dependent activity of polymorphonuclear blood leukocytes. It has been established that for patients with CCI I with high concentrations of IL-8, IL-10, SMNO and a low SEG index, the intake of Cereton and Actovegin or Ceraxon and Mexicor will be insufficient for effective correction of immunometabolic disorders, which requires additional administration of an immunomodulator. Patients with CCI II, who have a higher plasma level of TNFα, IL-10 and low SEG values, need to prescribe Ceraxon, Mexicor and Glutoxim or Ceraxon, Mexicor and Polyoxidonium in order to obtain the maximum clinical and laboratory positive effect.